Paralleles Sortieren auf mehrdimensionalen Gittern - Wanka, Rolf

Leistung eines Parallelrechners auf Basis des PowerPC-Prozessors - Simon, Jens (Parallele Datenverarbeitung aktuell: TAT '94)

Weak Sequential Composition in Process Algebras - Rensink, Arend; Wehrheim, Heike (CONCUR '94, Concurrency Theory, 5th International Conference, Uppsala, Sweden, August 22-25, 1994, Proceedings)

Parametric Action Refinement - Wehrheim, Heike (Programming Concepts, Methods and Calculi, Proceedings of the IFIP {TC2/WG2.1/WG2.2/WG2.3} Working Conference on Programming Concepts, Methods and Calculi {(PROCOMET} '94) San Miniato, Italy, 6-10 June, 1994)

Aussagenlogik - Deduktion und Algorithmen - Kleine Büning, Hans; Lettmann, Theodor

Endogenous Growth and R&D Models - A Critical Appraisal of Recent Developments - Gries, Thomas; Hentschel, C.; Wigger, B. (Jahrbücher für Nationalökonomie und Statistik)

MuPAD: Multi Processing Algebra Data Tool; Tutorial - Fuchssteiner, Benno; Gottheil, K.; Kemper, A.; Kluge, O.; Morisse, K.; Naundorf, H.; Oevel, Gudrun; Schulze, T.; Wiwianka, W.

MuPAD - new developments and their applications - Morisse, K.; Oevel, Gudrun (Computer Algebra in Science and Engineering)

Logic in Transition: The Logical Calculi of Hilbert (1905) and Zermelo (1908) - Peckhaus, Volker (Logic and Philosophy of Science in Uppsala. Papers from the 9th International Congress of Logic, Methodology and Philosophy of Science)
Rezensionen: MR 97h:03002 (E. Glas); Zbl. Math. 821.01021 (I. Grattan-Guinness)

Von Nelson zu Reichenbach. Kurt Grelling in Göttingen und Berlin - Peckhaus, Volker (Hans Reichenbach und die Berliner Gruppe)